2022
DOI: 10.1126/science.aay3325
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of mouse stem cells that can recapitulate the developmental potential of primitive endoderm

Abstract: The mammalian blastocyst consists of three distinct cell types: epiblast, trophoblast (TB), and primitive endoderm (PrE). Although embryonic stem cells (ESCs) and trophoblast stem cells (TSCs) retain the functional properties of epiblast and TB, respectively, stem cells that fully recapitulate the developmental potential of PrE have not been established. Here, we report derivation of primitive endoderm stem cells (PrESCs) in mice. PrESCs recapitulate properties of embryonic day 4.5 founder PrE, are efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
(17 reference statements)
1
12
0
Order By: Relevance
“…To further investigate the molecular features of ACL cultured cells, We compared ACL‐ESCs and ACL‐XEN cells with ESCs, TSCs, 67 XEN cells, 67 E4.5‐Epi 66 and E4.5_PrE. UHC analysis demonstrated that ACL‐ESCs were close to ESCs (Figure S3A ), in line with the IF staining and in vivo chimera assays results.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…To further investigate the molecular features of ACL cultured cells, We compared ACL‐ESCs and ACL‐XEN cells with ESCs, TSCs, 67 XEN cells, 67 E4.5‐Epi 66 and E4.5_PrE. UHC analysis demonstrated that ACL‐ESCs were close to ESCs (Figure S3A ), in line with the IF staining and in vivo chimera assays results.…”
Section: Resultssupporting
confidence: 65%
“… 65 HTSeq (0.6.1) was used for reads counting, and the RefSeq gene expression level was estimated using the reads per kilobase transcriptome per million reads (RPKM) method. In vivo data for mouse embryos E4.5 Epi (E‐MTAB‐2958), 66 E4.5 PrE, 66 ESCs (GSE119985), 60 TSCs 67 and XEN cells (GSE159181) 67 were downloaded and processed identically. DEGs in different samples were determined using the edgeR package, with a fold change ≥2 and p ≤ 0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a) and bulk RNA-seq (Supplementary Fig. 2b) show that genes such as Sox17, Gata4/6 are highly enriched in PrECLCs 16,17 . To see if these genes play any potential role in the bifurcating decision between pluripotent and PrE fates, we add each factor to JGES and show that Gata4 stands out as a critical inhibitor for pluripotent reprogramming (Fig.…”
Section: Bmp4 Diverts Cell Fate Toward Extra-embryonic Lineagesmentioning
confidence: 99%
“…This deep knowledge of the signaling milieu allowed researchers to recapitulate many stages of mouse and human embryonic development in vitro . By isolating cells from the mouse blastocyst, naïve pluripotent stem cells (mESC), trophoblast stem cells (mTSC) and extraembryonic primitive endoderm stem cells (nEnd) mimicking the ICM, the TE and the PrE respectively, can be obtained ( Tanaka et al, 1998 ; Ying et al, 2008 ; Anderson et al, 2017 ; Ohinata et al, 2022 ). Culture of naïve mESCs in vitro is achieved by the addition of GSK3β and MAPK/ERK inhibitors (2i) and leukemia inhibitory factor (LIF) in the so-called serum-free 2i/L media ( Ying et al, 2008 ).…”
Section: The Role Of Epigenetics In Regulating Early Embryonic Develo...mentioning
confidence: 99%